Recovery of nickel in the form of Ni(OH)2 from plating wastewater containing Ni-EDTA using bipolar membrane electrodialysis. (January 2023) - Liu, Yaoxing; Wu, Xiaoyu; Dai, Liping; Wu, Xiaoyun; Ding, Jianguo; Chen, Riyao; Ding, Rui; Liu, Jianxi; Van der Bruggen, Bart
Abstract: Ni is often present in plating wastewater as a complexing state. It is difficult to remove this Ni using traditional chemical precipitation technology. In this study, a bipolar membrane electrodialysis system was used to recover Ni in the form of Ni(OH)2 from plating wastewater containing Ni–ethylenediaminetetraacetic acid (Ni-EDTA) without adding chemical reagents. The stable structure of Ni-EDTA can be destroyed by H + produced by the bipolar membrane to obtain free Ni 2+, which can combine with OH − produced by the bipolar membrane to form Ni(OH)2 . When the electrolyte Na2 SO4 concentration, current density and initial Ni-EDTA concentration were 0.2 mol/L, 16 mA/cm 2 and 1000 mg/L, respectively, 99.0% of Ni-EDTA was removed after 32 h. When the system was used to treat actual plating wastewater, 92.1% of Ni-EDTA was removed and 88.7% was recovered. When the number of wastewater compartments in the system was increased from one to three, the current efficiency increased from 1.7% to 5.8%, and the specific energy consumption decreased from 0.39 to 0.19 kW h/g. The results of an X-ray diffraction study indicate that the Ni(OH)2 obtained in this study is similar to commercial Ni(OH)2 . Moreover, the recovery mechanism of Ni-EDTA was analysed. Thus, bipolar membrane electrodialysis can be regarded as an effective method to recover Ni from wastewater containing Ni-EDTA. Graphical abstract: Image 1 Highlights: A BMED system was fabricated to recover Ni from Ni-EDTA containing wastewater. Current density and electrolyte concentration have an obvious effect on Ni recovery. Ni-EDTA removal rate was 97.1% and the recovery rate of Ni was 95.2%. Purity of Ni(OH)2 recovered from an actual wastewater was 75.2%. Mechanism of recovering Ni was analyzed.